1971
DOI: 10.1021/ja00737a057
|View full text |Cite
|
Sign up to set email alerts
|

New synthesis of aldehydes via vinylsilanes

Abstract: We describe a new synthesis leading to aldehydes (and ketones).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(25 citation statements)
references
References 2 publications
1
23
0
1
Order By: Relevance
“…A) Stereoselective (cis + Z , fruns + E, ca. 95% ds) rearrangement of silyloxiranes to Si enol ethers [319,320]. B) Attack of an oxonium ion on a vinyl silane, leading to an oxepane via substitution with retention (R=Bu, R = H and R = H , R = B u , 98% ds) [321].…”
mentioning
confidence: 99%
“…A) Stereoselective (cis + Z , fruns + E, ca. 95% ds) rearrangement of silyloxiranes to Si enol ethers [319,320]. B) Attack of an oxonium ion on a vinyl silane, leading to an oxepane via substitution with retention (R=Bu, R = H and R = H , R = B u , 98% ds) [321].…”
mentioning
confidence: 99%
“…45 2.5. a-Trimethylsilyl epoxides a-Trimethylsilyl epoxides were introduced by Stork et al 46 who showed that epoxidation of a vinylsilane gave an a-trimethylsilyl epoxide. Magnus et al 48 introduced the formation of a-trimethylsilyl epoxides by chemistry that was closely analogous to the classical Darzens reaction.…”
Section: A-ester Epoxidesmentioning
confidence: 99%
“…[8] Vinylsilanes are well-known to be easily oxidized into α,β-epoxysilanes, which are useful intermediates for the preparation of carbonyl compounds. [9] It has also been shown that pure cis or trans α,β-epoxysilanes can be readily converted into heterosubstituted alkenes, such as vinyl halides, in high stereochemical purity. [10] Thus, the Z vinyl chloride 8 can be prepared in a simple way from vinylsilane 4e (E/ Z: 95:5) by oxidation, followed by treatment with HCl, in 59% overall yield (Scheme 3).…”
Section: Study Of the Carbometalationmentioning
confidence: 99%